Junior High School Teachers’ Difficulties in Implementing the PSP (Program Sekolah Penggerak) Curriculum - Mulyani Mulyani (Advances In Social Humanities Research, 2026)
Currently, Indonesia is implementing a new paradigm curriculum, namely the PSP (Program Sekolah Penggerak) curriculum (PSP) in junior high schools, particularly among English teachers, amid Indonesia’s ongoing curriculum reform efforts. Despite its implementation, the PSP curriculum has generated considerable concern, particularly regarding teachers’ capacity to adapt to its demands. However, in implementing this curriculum, there is a lot of attention from various parties, especially teachers. The purpose of the study is to analyze the difficulties faced by English teachers in implementing the PSP (Program Sekolah Penggerak) curriculum. The research only focused on junior high school teachers’ difficulties in implementing the PSP (Program Sekolah Penggerak) curriculum. The researcher limits the data of the study to teachers. This study employed the qualitative method as it was a more comprehensive account of the phenomenon under study would be presented. The research used a case study design. The participant consisted of two English teachers participants as the object of research. The instrument for collecting data was an interview. The type of interview used in this research is the semi-structured interview. To analyze the result of interviews this study used data reduction, data display, and conclusion. The first was the teacher’s understanding of the PSP curriculum. The second was the difficulties faced by English teachers. First, the difficulties faced were in terms of providing materials and teaching methods. Second, the teacher had difficulty managing time. Third, the difficulties faced by English teachers were the teaching devices. Fourth, the PSP curriculum was not implemented effectively and teachers had to be ready. The third was the advantages and disadvantages. The fourth was the differences between the PSP curriculum and the 2013 curriculum. The result of this study indicated that the teachers faced difficulties in providing materials and teaching methods, and had difficulty managing time, the teaching devices, effectiveness, and readiness.